2005
DOI: 10.1038/nature04161
|View full text |Cite
|
Sign up to set email alerts
|

Polar ocean ecosystems in a changing world

Abstract: Polar organisms have adapted their seasonal cycles to the dynamic interface between ice and water. This interface ranges from the micrometre-sized brine channels within sea ice to the planetary-scale advance and retreat of sea ice. Polar marine ecosystems are particularly sensitive to climate change because small temperature differences can have large effects on the extent and thickness of sea ice. Little is known about the interactions between large, long-lived organisms and their planktonic food supply. Dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
310
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 430 publications
(317 citation statements)
references
References 50 publications
5
310
1
1
Order By: Relevance
“…Ironically, these humaninduced changes to the atmosphere have mitigated the southward penetration of global warming around Antarctica (Fyfe et al, 1999;Marshall, 2003;Turner et al, 2009;Swart and Fyfe, 2012). However, the continuing release of greenhouse gasses and the recovery of the ozone hole will inevitably cause future climate-induced warming and ecosystem change in Antarctic waters (Smetacek and Nicol, 2005;Boyd et al, 2008;Constable et al, 2014). Warming temperatures will unavoidably result in a decline in sea ice duration, extent and thickness (Constable et al, 2014 and refs therein).…”
Section: Climate-driven Changes To the Southern Oceanmentioning
confidence: 99%
“…Ironically, these humaninduced changes to the atmosphere have mitigated the southward penetration of global warming around Antarctica (Fyfe et al, 1999;Marshall, 2003;Turner et al, 2009;Swart and Fyfe, 2012). However, the continuing release of greenhouse gasses and the recovery of the ozone hole will inevitably cause future climate-induced warming and ecosystem change in Antarctic waters (Smetacek and Nicol, 2005;Boyd et al, 2008;Constable et al, 2014). Warming temperatures will unavoidably result in a decline in sea ice duration, extent and thickness (Constable et al, 2014 and refs therein).…”
Section: Climate-driven Changes To the Southern Oceanmentioning
confidence: 99%
“…Either it will be grazed and recycled in the upper water masses or it may sink to deeper waters (Wassmann 1998). Recent research has also emphasized the importance of nanoplankton and picoplankton (Lovejoy et al 2007;Sakshaug et al 2009;Rokkan Iversen and Seuthe 2010) and showed that the concept of short, low-diversity polar food chains is overly simplistic (Smetacek and Nicol 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in Arctic sea ice in response to climate change and ocean warming is well documented ), but its effects on biological processes are hard to predict (ACIA 2004;Smetacek and Nicol 2005). Wassmann et al (2011) highlighted that climate change has already resulted in clearly discernable changes in marine Arctic ecosystems, but the number of well-documented changes in planktonic and benthic systems was surprisingly low.…”
Section: Introductionmentioning
confidence: 99%